Alterations in neuronal control of body weight and anxiety behavior by glutathione peroxidase 4 deficiency. (15th August 2017) - Schriever, Sonja C.; Zimprich, Annemarie; Pfuhlmann, Katrin; Baumann, Peter; Giesert, Florian; Klaus, Valentina; Kabra, Dhiraj G.; Hafen, Ulrich; Romanov, Artem; Tschöp, Matthias H.; Wurst, Wolfgang; Conrad, Marcus; et al.
Graphical abstract: Highlights: Gpx4 deletion from dopaminergic neurons leads to symptoms of PD-like anxiety. Gpx4 and DJ-1 co-deletion from dopaminergic neurons decreases spontaneous locomotion. HFHS diet exposure attenuates hypothalamic Gpx4 expression and activity in mice. HFHS-fed Gpx4 AgRP-Cre KO males show increased weight gain and reduced locomotion. Abstract: Elevated levels of oxidative stress and neuronal inflammation in the hypothalamus or ventral midbrain, respectively, represent common denominators for obesity and Parkinson's Disease (PD). However, little is known about defense mechanisms that protect neurons in these regions from oxidative damage. Here, we aimed to assess whether murine Gpx4, a crucial antioxidant enzyme that protects neurons from membrane damage and ferroptosis, is critical for the protection from neuronal inflammation in two distinct pathophysiologic diseases, namely metabolic dysfunction in diet-induced obesity or PD. Gpx4 was deleted from either AgRP or POMC neurons in the hypothalamus, essential for metabolic homeostasis, or from dopaminergic neurons in the ventral midbrain, governing behaviors such as anxiety or voluntary movement. To induce a pro-inflammatory environment, AgRP and POMC neuron-specific Gpx4 knockout mice were subjected to high-fat high-sucrose (HFHS) diet. To exacerbate oxidative stress in dopaminergic neurons of the ventral midbrain, we systemically co-deleted the PD-related gene DJ-1. Gpx4 was dispensable for the maintenance of cellular health and function of POMC neurons, even in mice exposed to obesogenic conditions. In contrast, HFHS-fed mice with Gpx4 deletion from AgRP neurons displayed increased body adiposity. Gpx4 expression and activity were diminished in the hypothalamus of HFHS-fed mice compared to standard diet-fed controls. Gpx4 deletion from dopaminergic neurons induced anxiety behavior, and diminished spontaneous locomotor activity when DJ-1 was co-deleted. Overall, these data suggest a physiological role for Gpx4 in balancing metabolic control signals and inflammation in AgRP but not POMC neurons. Moreover, Gpx4 appears to constitute an important rheostat against neuronal dysfunction and PD-like symptoms in dopaminergic circuitry within the ventral midbrain.